Effect of a physical education program in early childhood education on the performance of fundamental movement skills based on teaching styles: divergent discovery and practical - Daniela Bartolo; Fernando Garbeloto; Osvaldo Ferraz (IP Iermakov S.S., 2024)
Background and Study Aim. Various proposals suggest that Physical Education classes (PE) should prioritize the development of fundamental movement skills (FMS), particularly in preschool children. Despite the crucial nature of mastering FMS, there is a paucity of evidence regarding the impact of PE classes on FMS development. The primary objective of this study is to investigate the effect of a physical education program on the performance of preschool students with varying levels of development in fundamental movement skills, employing divergent discovery and practical teaching styles. Material and Methods. Seventy-seven children (35 boys), aged between 4.5 and 6 years were divided into three groups: Control Group (CG) with 25 participants, Divergent Discovery Group (DDG) with 24 participants, and Practice Group (PG) with 28 participants. The intervention program spanned six months, with two 50-minute classes per week for the experimental groups. Conversely, the control group participated in the Classroom Program proposal. All three groups underwent the TGMD-3 motor test. Performance measurement involved the sum of the raw score in the locomotor and object control classes. Results. The findings revealed that the Control Group, Divergent Discovery Group, and Practice Group exhibited improved FMS performance from pre to post. Concerning intergroup differences, no significant disparities were observed in the pre-test. However, post-intervention results indicated that both the Divergent Discovery Group and Practice Group demonstrated superior FMS performance compared to the Control Group. Conclusions. Physical Education classes for Early Childhood Education play a crucial role in fostering significant effects on children's motor development when offered in an appropriate context and through a systematically structured intervention.